DYSBIOTIC CHANGES IN PATIENTS WITH STROKE: ANALYSIS BASED ON ARTIFICIAL INTELLIGENCE AND TELEMEDICINE APPROACHES (KIUT Publication, 2025)
According to the analysis results of the Ministry of Health of the Republic of Uzbekistan and scientific publications, more than 60,000 cases of stroke (acute cerebrovascular disorder) are registered annually in Uzbekistan. Moreover, post-stroke disability accounts for 83.3% of cases, and the hospital mortality rate is 17.7%. According to the World Health Organization, in economically developed countries, stroke ranks third among the causes of death, preceded only by cardiovascular diseases and cancer.